PRAWO RZYMSKIE W INTERNECIE - Służewska, Zuzanna (Zeszyty Prawnicze, 2017)
ROMAN LAW ON THE INTERNET Summary In the past ten years the Internet has become a very popular information exchange tool serving people around the world. A summary review of information included on the world wide web indicates that the Internet constitutes a rich and diversified source of information about certain issues, which enables not only the popularisation of such knowledge, but also creates an open forum for the discussions of many different issues. There are also many sites on Roman on the Internet, which were created not only by the universities and other scientific centres, but also by private individuals interested in Roman law as a hobby. O f course, such web sites are either currently not very large and devoted to specific problems of Roman law, or very general and thus not of much use for romanists interested in specific issues. Also the catalogue of sources of Roman law that is available on the net is still incomplete, which probably results from the problems connected with the transformation of original source texts into electronic form. In this article I would like to present the results of my „web surfing”, in order to encourage Roman law researchers to use the Internet as a serious source of information, and to show that the Internet may provide enormous possibilities in the future. The various sites devoted to Roman law existing on the Internet may be divided into some general categories depending on the type and purpose of each of these sites. The first type or category consists of Internet sites created by universities, law school and other educational centres. The information included therein is mainly of an administrative nature and refers to the programme of studies, exam schedules, academic teachers and tutors and similar matters not connected with Roman law itself. Some of them also give information about special projects conducted in this particular school and information about local libraries with lists of available books. Apart from the private sites created by the members of the academic community on the web one can find also the sites created by individual people, who publish on the Internet the results of their research, their opinions on different legal problems connected with Roman law, summaries of books devoted to Roman law an so forth. The next category of Internet sites that may be used by a person studying Roman law are sites that include texts of legal sources. This kind of site, although not including much substantial information on Roman law, may be helpful for the researcher of antiquity and Roman law as it enables easy access to the text of selected source. Last of all I would like to pay some attention to Internet sites devoted to ancient Rome in general, not necessarily to Roman law. The sites of this kind are more popular science than strictly scientific materials, and probably they are not of much use for the historians of antiquity. On the other hand, they include some interesting pieces of information neither being taught in standard course of studies nor included in history manuals, bringing the realities of ancient world closer to us, such as information on Roman cuisine, Roman coins, or Roman clothes. These sites also include a large variety of pictures and photos, which makes them more attractive for visitors. As we can see the Internet has become quite a rich source of information about antiquity and Roman law. Taking into consideration all the advantages that this global network offers in the field of transferring and broadcasting information, certainly it is worthy of greater attention on the part of romanists. Since the information included therein is relatively general, the primary use of the Internet by romanists should be in my opinion as an educational tool. Encouraging students to use the Internet while learning Roman law may inspire them to more detailed studies on selected subjects, not limited to information included in popular manuals and, as the next step, in creating their own www sites devoted to particular problems in the field of Roman law. Simultaneously no less of importance is co-operation among romanists from all countries in order to make the Internet useful also for the researcher of Roman law. That could be achieved through placing texts of scholar books and articles on the web, creating the universities’ homepages devoted to Roman law, initialising collaborative Internet projects and presenting the individuals achievements in the field of Roman law on the net. As a result in a few years it could be expected that the Internet would become the compendium of information on Roman law, widely available and easy to use, as well as the forum of collaboration among academia in the field of Roman law. In the modern world, where history knowledge is often treated as an useless ballast, especially the researchers of antiquity should make use of technical innovations in the field of dissemination of information because it enables their knowledge to survive. Providing the virtual reality has become the constant element of everyday life, the reservation of space on the Internet for Roman law is the way to make Roman law in some sense „immortal”.